The effects of positive leadership on quality of work and life of family doctors: The moderated role of culture - Sun, Wei; Huang, Xianhong; Chen, Xingyu; Wu, Yan; Huang, Zhen; Pang, Yichen; Peng, Can; Zhang, Yunjie; Zhang, Hao (Frontiers in Psychology, 2023)
Quality of work and life (QWL) of family doctor is high valued in improving access and equity of healthcare, however, the current low level of QWL in many countries and regions needs to be improved urgently. Under the above background, via analysis of data from 473 valid questionnaires of family doctors in China as a sample and with SEM, hierarchical linear regression, simple slope test, this study explored the effect of positive leadership on the QWL of family doctors, as well as the moderating role of culture. The empirical results show that positive leadership promoted the QWL of family doctors by motivating their achievement motivation and coordinating supportive resources. In addition, our hierarchical linear regression analysis found that the interactive items of positive leadership and culture had a positive effect on achievement motivation (β(a) = 0.192), QWL (β(b) = 0.215) and supportive resources (β(c) = 0.195). Meanwhile, culture had a moderated mediating effect on the relationship between positive leadership and QWL via the achievement motivation of family doctors and supportive resources. These findings suggest that the interaction among multiple factors, including environmental factors, individual physiological features and culture, may influence the impact of positive leadership on the QWL of family doctors. The possible reasons for these findings and theoretical and practical implications are discussed in this study.